Effect of Bonding Application Time on Bond Strength of Composite Resin to Glass Ionomer Cement - Narges Panahandeh; Hassan Torabzadeh; Amir Ghassemi; Mina Mahdian; Alireza Akbarzadeh Bagheban; Seddigheh Moayyedi (Tehran University of Medical Sciences, 2016)
Objectives: This experimental study evaluated the effect of bonding application time on the microshear bond strength of composite resin to different types of glass ionomer cements (GICs). Materials and Methods: One-hundred and sixty specimens (two conventional and two resin-modified GICs) were prepared and divided into 16 groups. The surface of all specimens was prepared using two different bonding systems (Frog and Stea) at three different times. After setting, the composite resin (Z100) was placed over the GICs. The specimens were then stored in distilled water for 24 hours (37oC) and exposed to microshear stresses at a crosshead speed of 1 mm/min. The results were analyzed using three-way ANOVA and Tukey's test (P˂0.05). Results: In conventional GICs, bond strength was affected by the type of bonding system at different times, and bond strength was significantly higher in the Fuji II group compared to Riva Self Cure group. In the Riva Self Cure group, bond strength was significantly affected by time; whereas, the type of bonding system failed to exert a significant effect on bond strength. There was no significant correlation between the type of bonding system and the two brands of resin-modified GICs. Bond strength was not affected by the type of bonding agent; however, among the two brands of resin-modified GICs, Fuji II LC yielded a significantly stronger bond. Conclusion: It appears that the type of bonding agent does not affect the microshear bond strength, and the bonding application time affects the microshear bond strength in Riva Self Cure GICs.